PENGARUH BEASISWA DAN MOTIVASI BELAJAR TERHADAP PENINGKATAN PRESTASI SISWA (STUDI KASUS SMPIT MADANI PEKANBARU) - Fitri khairunnisak; Rina Selva Johan; RM. Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is aimed to know the influence of scholarship and Motivation of learning on student learning achievement of SMPIT Madani School Pekanbaru. The method use the research was quantitavive descriptive method. The population in this research was all of the student in SMPIT Madani Pekanbaru that has 101 peoples. Determination of total sample use simple random sampling technique, which has 50 student. the data used were primary data through the spread of questionare and the secondary data through the first semester grade of Indonesian languange, English, Matehematic, Exact science, and Social sciece in academic year 2015/2016. the data analisys technique use was regression. Based on the reseach result, it could scholarship and mativation of learning influence the student learning echievement simultaneously. The influence of scholarship and motivation or learning on student echievement in SMPIT Madani Pekanbaru was 85 %.Key Word: Scholarship, Motivation of Learning, learning echievement